Analysis of the biogas content of tofu solid waste with the addition of urea - Almiatun Ratu Darati; Suwati Suwati; Nur Annisa Istiqamah; Muanah Muanah; Basirun Basirun (Universitas Muhammadiyah Mataram, 2025)
Biogas production by fermentation is a source of energy obtained from organic waste, one of which is waste from the tofu and tempeh industry. The aim of this study was to analyze the biogas content of tau waste by adding urea. The research method uses an experimental method with a Completely Randomized Design. There were four treatments, namely T1: 7 kg of tofu waste, T2: addition of 7 kg of tofu waste + 1.4 kg of urea starter, T3: addition of tofu waste + 2.8 kg of urea starter, and T4: addition of 7 kg of tofu waste + urea starter as much as 4.2 kg. Each treatment was repeated 3 times to obtain 12 experimental units. The statistical test results show that the biogas content, in this case carbon dioxide and methane gas, with the highest measurement results found in T1 was 3819.17 ppm, and methane gas was 558.08 mol.